Índios e criollos : rapto e aprisionamento : características do cativeiro nas fronteiras pampiano-patagônicas no século XVIII - Silva, Marcelo Augusto Maciel da (Universidade do Vale do Rio dos Sinos, 2018)
This study addresses the captivity theme, based on the Indians and hispanic-criollo imprisonment cases, that occurred throughout the 18th century, in the South of Buenos Aires. Despite the fact that the imprisonment of captives could exist between the Indians parties even before the Spaniards' arrival, were the latter that held more prisoners. Therefore, inserting those captures in the context of colonial advance, we look to explore the reasons and arguments used by the Spaniards to justify such captures, as well as investigate the destinations where the indigenous population were routed. In addition, we try to approach from a perspective that explain the abduction and captivity role for the native societies studied here. Regarding to what was practiced by the Indians, we propose to segregate the abduction from captivity, and approach each issue from their own particularities. For the hispanic, the capture of indigenous prisioners had official objectives, directed to the conversion, safety and acquisition of new land. Among the natives, the capture would complement family economic practices. The captivity itself would come to be an outcome, resulting from the attacks conducted against the natives for the first, but for these, the captivity was the own purpose of imprisonment.
Keywords: Rapto; Cativeiro; Cativos; Hispânicos; Indígenas; Abduction; Captivity; Captives; Hispanics; Indigenous people; ACCNPQ::Ciências Humanas::História